'Quoting' minorities in Viet performing arts - a short history of musical subordination. - Jaehnichen, Gisa (Institut für Volksmusikforschung und Ethnomusikologie, 2012)
Indochina is the home of about a million so-called “Moi” wrote Joseph Buttinger in 1968 and referred to the Vietnamese term for “savages”. Now, this classification is not longer officially appreciated. Nevertheless, the history of minority cultures sharing a huge territory with a strong majority such as the Viet reaches far back into the past. We find marks of cultural exchange in many aspects of Viet performing arts such as song competitions, ritual music, instrumental entertainment, traditional theatre, and also in ‘classical’ vocal and instrumental compositions including their commercially and nationally motivated presentation. Illustrating these cultural contacts and their various appearances rooted in the past centuries with some clear examples from the author’s own long term field researches, the paper will discuss the way of quoting minority cultures, the respective level of individuality, the background of the quoted musical reference, and the level of identification among the bearer of these quoted cultures. Do they feel being respected as group and/or as personalities? Do those quotations change their musical self-presentation? Does knowledge about their inter-related music histories helps to find mutual musical understanding? These and other questions will be discussed.